Finite Element Analysis of Steel Quenching Process - Salem Hamouda, Abdel Magid; Lau, C. K. (Universiti Putra Malaysia Press, 2001)
The finite element method (FEM) is employed to investigate the residual stress state and the variation of internal stresses in the St5O cylinder bar quenched from 600 to O°C. Thermal analysis is first performed to obtain the cooling curves for the core and surface of the bar, this is followed by a full structural analysis. The results obtained from the computer simulation are compared with those experimentally determined values that are available in the literature and there appears to be a good measure of agreement. The study found that at the initial stages of the quenching process, the residual stresses were tensile at the surface and compressive in the core, however, towards the end of the quenching process, the tensile residual stresses switched to the core and compressive residual stresses at the surface.